Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/1759720x20975915
|View full text |Cite
|
Sign up to set email alerts
|

Skin manifestations in spondyloarthritis

Abstract: Spondyloarthritides (SpA) like psoriatic arthritis, axial spondyloarthritis/ankylosing spondylitis, reactive arthritis and inflammatory bowel disease (IBD)-associated SpA can present with characteristic skin manifestations. These SpA-associated skin disorders may precede joint involvement, reflect a loss of efficacy of a current systemic treatment or can even be treatment associated. Cutaneous manifestations in SpA not only add additional morbidity with physical impact but also impose a psychosocial burden on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 235 publications
0
11
0
Order By: Relevance
“…They may include Keratoderma blenorrhagicum, circinate balanitis, ulcerative vulvitis, oral lesions, and nail changes 11,12 . Keratoderma blenorrhagicum typically appears as erythematous macules and papules in the plantar and palmar area, rising into vesicular, often hyperkeratotic plaques and sterile pustules 3 . Only 10% of ReA patients with positive HLA‐B27 develop these lesions 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may include Keratoderma blenorrhagicum, circinate balanitis, ulcerative vulvitis, oral lesions, and nail changes 11,12 . Keratoderma blenorrhagicum typically appears as erythematous macules and papules in the plantar and palmar area, rising into vesicular, often hyperkeratotic plaques and sterile pustules 3 . Only 10% of ReA patients with positive HLA‐B27 develop these lesions 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestations include mucocutaneous manifestations such as keratoderma blenorrhagicum, circinate balanitis, ulcerative vulvitis, nail changes (dystrophy and thickness), oral lesions, and conjunctivitis. 2,3 The main rheumatological manifestations are asymmetric oligoarticular arthritis of the lower limbs, enthesitis, dactylitis, and inflammatory back pain.The diagnosis of ReA is challenging since no diagnosis criteria are available. We report a case of ReA occurring…”
mentioning
confidence: 99%
“…Patients with AS can present impairments accompanied by pain and a decrease in both function and QoL, such as axial involvement, tyoical skin manifestations, altered gait kinematics, higher risk of uveitis, and dactylitis, pulmonary function impairments, and decrease in exercise capacity. [1][2][3][4][5] It has been shown that peripheral arthritis observes in about a third of cases, with asymmetrical involvement of one large joint like the hip, knee, or shoulder. [2] Recent studies have demonstrated that symptomatic enthesopathy of the shoulder is common in patients with AS, and coxitis is the only predictive factor for shoulder enthesitis.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] It typically affects the axial joints, most notably the sacroiliac joints; however, other sites of involvement, including peripheral joints and extra-articular manifestations, are also observed. [3][4][5] Pharmacological management of AS includes disease-modifying anti-rheumatic drugs (DMARDs) such as anti-tumor necrosis factor (TNF) agents to control the disease progression. However, patients with AS may still present impairments accompanied by pain and decreased function and quality of life (QoL).…”
mentioning
confidence: 99%
See 1 more Smart Citation